Training on Electrical Welding Engineering for Airport Environment Force III - Masito, Fitri; Sukahir, Sukahir; M Soleh, Asep; Sunardi, Sunardi; Rukmana, Ganda; Wulandari, Retno Sawitri; Anes, Alfian Meidy (CV Media Inti Teknologi, 2023)
The training aims to enable participants to equip participants with trained, skilled, and tested abilities in electric welding. The training is designed to accommodate a total of 42 lesson hours and will take place over five days from March 13 to March 17, 2023. The face-to-face learning method is employed at Atung Bungsu Airport in Pagar Alam to facilitate practical activities using actual equipment in the field. The theoretical learning sessions are conducted on-site, allowing participants and instructors to remain at the location throughout the training. Face-to-face interactions, discussions, and questions are facilitated during the scheduled sessions, while additional communication is maintained through a WhatsApp Group. The practical session takes place after participants have completed the theory session and passed the theory exam. It is held in the Atung Bungsu Airport environment, where participants actively engage in hands-on activities. Strict adherence to health protocols is maintained throughout the learning activities. Assessment of learning outcomes is based on participants' attendance records and comprehensive exam results, ensuring a comprehensive evaluation of their progress and performance.